Canção e Dansa para contrabaixo e piano de Radamés Gnattali: aspectos históricos, estudo analítico e edição - Ricardo Pereira Rodrigues (2003)
Abstract: Analysis and edition of Canção e Dansa by RadamésGnattali, an important landmark of the Brazilian repertory for the doublebass, through the study of the autographed manuscripts of 1934 and 1982 and also the score published by the now extinct Brazilian cultural agency FUNARTE. It icludes historical aspects of the composer and his relationship with doublebassists, the work in question and the double bass literature in general. In spite of the formal simplicity of the works, Canção e Dansa presents some sophisticated procedures, derived from Brazilan popular music and jazz, which can be observed in harmony, motives and rhythm. The analysis helped the suggestion of bowings and fingerings included in the edition. It also includes a non commercial recording with the work and interviews with Brazilian double bassists Sandrino Santoro e Renato Sbragia.